Oncological outcomes of salvage cryotherapy after primary radiation therapy vs. primary cryotherapy: 10-year experience at a large Canadian referral center - Alexandra Bain; Kinnaird, Adam; McLarty, Ryan; Senthilselvan, Ambikaipakan; Todd, Gerald; Chetner, Michael P. (Canadian Urological Association Journal, 2020)
Introduction: Salvage cryotherapy is a guideline-recommended treatment of localized prostate cancer recurrence after radiation therapy. There is little published evidence analyzing the outcomes of salvage cryotherapy for recurrent prostate cancer following different primary therapy energy modalities. Methods: We performed a retrospective analysis of patients who received whole gland salvage cryotherapy from 2007–2017 at a large tertiary referral center after either primary radiation therapy (RT) or primary whole gland cryotherapy. Primary outcome was biochemical failure, defined as per the Phoenix criteria (prostate-specific antigen [PSA] nadir + 2.0 ng/ml). Secondary outcomes included time to biochemical failure and development of metastatic disease. Results: Fifty-eight of 391 patients who received cryotherapy were identified as having received salvage cryotherapy (after RT, n=37; after primary cryotherapy, n=21). Biochemical recurrence occurred in 21 (57%) patients with previous RT and in 17 (81%) patients with previous cryotherapy (p=0.001). Median time to biochemical recurrence was 18 months for patients with previous RT and 13 months for patients with previous cryotherapy (p=0.002). The biochemical-free survival rate for primary radiation therapy patients was 71% at two years compared to 23% at two years for patients who underwent primary cryotherapy (p<0.01). There was no difference in the development of metastatic disease between groups (19% vs. 18%, cryo vs. radiation, p=0.34). Conclusions: These results suggest that salvage cryotherapy may offer more durable oncological control to patients after radiation compared to primary cryotherapy, with a lower rate and longer duration before biochemical recurrence.